Causes of Truancy in Debre Markos Preparatory Secondary School - Liyew, Addisu (The Ethiopian Journal of Education, 2021)
Truancy which refers to students’ action of staying away from some or all lessons after they are marked officially present at school is becoming one of the serious problems of schools today. This study examined the causes of truancy in Debre Markos Preparatory Secondary School. In order to achieve the objectives, data were gathered from truants, regularly attending students, and teachers through interviews. The qualitative analysis of the data gathered through interview revealed that truancy is linked with high family socio-economic status, strict control at home and school, the social context of the school, plasma instruction, lack of motivation and disinterest in learning, etc.